Evaluating robotic assistance on the learning curve and efficiency of mandibular angle ostectomy: an animal model study - Han, Wenqing; Yan, Yingjie; Sun, Mengzhe; Zhang, Ziwei; Lin, Li; Zhang, Yan; Chai, Gang (Frontiers in Surgery, 2024)
IntroductionThis study evaluated the efficacy and learning curve of a maxillofacial surgical robotic system (MSRS) guided by electromagnetic navigation for mandibular angle ostectomy (MAO), compared to traditional surgical methods.MethodsThe study utilized a controlled experiment involving thirty rabbits, paired divided into experimental and control groups. The experimental group underwent MAO using the MSRS, while the control group was treated with conventional surgical techniques. The surgeons performing the procedures were inexperienced in robotic surgery and MAO to assess the learning curve and the impact of robotic assistance. Key parameters measured included the accuracy of ostectomy, setup time, and ostectomy efficiency, with data analyzed through a paired-t test to compare the performance between the two groups.ResultsThe study indicated a significant reduction in ostectomy time for the experimental group, with improved accuracy and efficiency in ostectomy. The study found that robotic assistance could decrease the risk of complications and enhance surgical outcomes. It also highlighted the presence of an initial learning curve when adopting new robotic technologies, which could be mitigated through adequate training and simulation practices.DiscussionUsing MSRS for MAO could lead to faster early learning curves and increased ostectomy efficiency compared to traditional surgical methods. It demonstrated the potential benefits of integrating robotic systems into craniofacial surgery, suggesting a promising direction for future surgical practices.